Properties of proteolytic enzyme from ginger (Zingiber officinale Roscoe) - Nafi, Ahmad; Foo, Hooi Ling; Bakar, Jamilah; Mohd Ghazali, Hasanah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Proteases in ginger rhizome have the potentials in industrial applications. This study was conducted to extract and characterize the proteolytic enzyme from ginger ( Zingiber officinale Roscoe). Ginger protease (GP) was extracted from ginger rhizome by homogenization with 100 mM potassium phosphate buffer pH 7.0 containing 10 mM cysteine and 5 mM EDTA which were found to be the most efficient extraction buffer and stabilizers. After centrifugation at 10,500 x g, protein in the crude extract was precipitated using 60% ammonium sulfate following which the precipitate was redissolved in 50 mM potassium phosphate buffer pH 7.0, dialyzed and then lyophilized. The extraction method yielded 0.94% (w/w of fresh weight) of GP with a specific activity of 27.6 ± 0.1 Unit/mg protein where 1 Unit is defined as the amount of protease causing an increase in absorbance by 1 unit per minute using azocasein as the substrate. Results show that the GP was completely inhibited by heavy metal cations i.e. Cu 2+ and Hg 2+ , and a thiol blocking agent or inhibitor, n-ethyl maleimide (NEM), indicating that GP is most probably a cysteine protease. The enzyme has an optimum temperature at 60 o C and the optimum pH ranged between pH 6 to 8. Monovalent cations (K + and Na + ) have no significant effect on activity of GP, but divalent and trivalent cations showed moderate inhibitory effect. Detergents such as sodium dodecyl sulfate increased the activity of GP while Tween 80 and Tween 20 slightly reduced the activity.